2018
DOI: 10.3748/wjg.v24.i22.2373
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Helicobacter pylori infection in atrophic gastritis

Abstract: Helicobacter pylori (Hp) is a major human pathogen causing chronic, progressive gastric mucosal damage and is linked to gastric atrophy and cancer. Hp-positive individuals constitute the major reservoir for transmission of infection. There is no ideal treatment for Hp. Hp infection is not cured by a single antibiotic, and sometimes, a combined treatment with three or more antibiotics is ineffective. Atrophic gastritis (AG) is a chronic disease whose main features are atrophy and/or intestinal metaplasia of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 65 publications
1
47
0
4
Order By: Relevance
“…Many studies have reported that H. pylori eradication contributes to improving gastric mucosal atrophy. [17][18][19] Previously, we also reported that the H. pylori eradication ameliorates the risk of development of metachronous gastric neoplasia in patients who underwent endoscopic resection, and it was associated with elevated serum PG I/II ratios in the follow-up, suggesting that the eradication improved the gastric mucosal status. 16 In addition, several studies have attempted to show whether changes in serum PG was related to successful bacterial eradication.…”
Section: Discussionmentioning
confidence: 88%
“…Many studies have reported that H. pylori eradication contributes to improving gastric mucosal atrophy. [17][18][19] Previously, we also reported that the H. pylori eradication ameliorates the risk of development of metachronous gastric neoplasia in patients who underwent endoscopic resection, and it was associated with elevated serum PG I/II ratios in the follow-up, suggesting that the eradication improved the gastric mucosal status. 16 In addition, several studies have attempted to show whether changes in serum PG was related to successful bacterial eradication.…”
Section: Discussionmentioning
confidence: 88%
“…Согласно рекомендации ACG, при лечении пациентов с БК препараты выбираются на основе клинических проявлений и прогноза пациента [28]. Несмотря на то что ИПП могут использоваться в качестве первоначального лечения желудочных поражений при БК [22], их эффективность в лечении подобных поражений остается спорной [42,43]. Различия в определении конечных целей лечения, таких как улучшение симптомов или заживление слизистой оболочки, могут быть одной из причин этого противоречия.…”
Section: рис 4 результаты повторного гистологического исследованияunclassified
“…У нашей пациентки ИПП не использовались в связи с ее отказом принимать данные препараты из-за отсутствия выраженного клинического эффекта в купировании синдрома абдоминальной боли и желудочной диспепсии на начальных этапах лечения. Кроме того, у пациентки имело место снижение секреторной функции желудка (снижение пепсиногена I и гипергастринемия), определялась умеренная атрофия желез и крупноочаговая кишечная метаплазия эпителия желудка при гистологическом исследовании желудочных биоптатов, что также ограничивает использование ИПП [43].…”
Section: рис 4 результаты повторного гистологического исследованияunclassified
“…Helicobacter pylori (Hp) is recognized as an important human pathogen that colonizes the gastric mucus resulting in super cial gastritis, atrophic gastritis and gastric cancer [1][2][3] . Present treatments for Hp infection include proton pump inhibitors or bismuth in combination with amoxicillin or metronidazole and clarithromycin [4][5] . The rate of drug resistance is increasing due to a wide range of use of antibiotics and high resistance rates to clarithromycin, metronidazole and levo oxacin are associated with the failure of Hp eradication [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%